Interpreting clinical trial data in multiple myeloma: translating findings to the real-world setting - Richardson, Paul G; San Miguel, Jesus F; Moreau, Philippe; Hajek, Roman; Dimopoulos, Meletios A; Laubach, Jacob P; Palumbo, Antonio; Luptakova, Katarina; Romanus, Dorothy; Skácel, Tomáš; Kumar, Shaji K; Anderson, Kenneth C (Blood cancer journal, 2018)
Substantial improvements in survival have been seen in multiple myeloma (MM) over recent years, associated with the introduction and widespread use of multiple novel agents and regimens, as well as the emerging treatment paradigm of continuous or long-term therapy. However, these therapies and approaches may have limitations in the community setting, associated with toxicity burden, patient burden, and other factors including cost. Consequently, despite improvements in efficacy in the rigorously controlled clinical trials setting, the same results are not always achieved in real-world practice. Furthermore, the large number of different treatment options and regimens under investigation in various MM settings precludes the feasibility of obtaining head-to-head clinical trial data, and there is a temptation to use cross-trial comparisons to evaluate data across regimens. However, multiple aspects, including patient-related, disease-related, and treatment-related factors, can influence clinical trial outcomes and lead to differences between studies that may confound direct comparisons between data. In this review, we explore the various factors requiring attention when evaluating clinical trial data across available agents/regimens, as well as other considerations that may impact the translation of these findings into everyday MM management. We also investigate discrepancies between clinical trial efficacy and real-world effectiveness through a literature review of non-clinical trial data in relapsed/refractory MM on novel agent-based regimens and evaluate these data in the context of phase 3 trial results for recently approved and commonly used regimens. We thereby demonstrate the complexity of interpreting data across clinical studies in MM, as well as between clinical studies and routine-care analyses, with the aim to help clinicians consider all the necessary issues when tailoring individual patients' treatment approaches.
Keywords: Comorbidity; Treatment Outcome; Multiple Myeloma; Neoplasm Staging; interpretace statistických dat; prognóza; výzkumný projekt; komorbidita; Healthcare Disparities; klinické zkoušky jako téma; lidé; staging nádorů; Prognosis; Clinical Trials as Topic; výsledek terapie; Research Design; Humans; mnohočetný myelom; Data Interpretation, Statistical; disparity zdravotní péče